1972
DOI: 10.1901/jeab.1972.18-79
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Negative Discriminative Stimulus as a Reinforcer of Observing

Abstract: Five pigeons were used to test the hypothesis that the source of reinforcement for observing behavior is the information that it provides concerning the schedule of primary reinforcement. On a variable-interval schedule, pecking the left-hand key produced a 30-sec display of such information. During this 30-sec period, when pecking the right-hand key was reinforced on a random-interval schedule, both keys were green; when no reinforcement was scheduled (extinction) both keys were red. Later, this baseline proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
91
1
4

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 5 publications
10
91
1
4
Order By: Relevance
“…Thus, observing responses would have been reinforced continuously during fading but only intermittently during traditional discrimination training. By the end of the training in Condition B, then , observing behavior would have been strengthened more by fading than by traditional discrimination training (deLorge & Clark, I 971 ; Dinsmoor, Browne, & Lawrence, 1972). In Condition C, it follows that subjects should observe the relevant features of the stimuli more readily after fading than after traditional discrimination training and, thus, learn C in fewer trials after fading.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, observing responses would have been reinforced continuously during fading but only intermittently during traditional discrimination training. By the end of the training in Condition B, then , observing behavior would have been strengthened more by fading than by traditional discrimination training (deLorge & Clark, I 971 ; Dinsmoor, Browne, & Lawrence, 1972). In Condition C, it follows that subjects should observe the relevant features of the stimuli more readily after fading than after traditional discrimination training and, thus, learn C in fewer trials after fading.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, results have been mixed. Dinsmoor et al (1972) found a small and inconsistent increase in observing when only S+ could be produced. However, using rhesus monkeys as subjects, Lieberman (1972) found a decrease in observing rates when S -was omitted, and a similar result has been found using pigeons (Mueller & Dinsmoor, 1984).…”
mentioning
confidence: 97%
“…In addition, however, the occurrence of the responses themselves demanded explanation. In Wyckoff's procedure (1969), in similar operant procedures (e.g., Dinsmoor, Browne, & Lawrence, 1972), and in procedures using an E maze (e.g., Prokasy, 1956), the occurrence of observing responses did not affect the delivery of food. For example, in operant procedures using interval-based food reinforcement schedules, subjects respond at rates sufficient to collect all food reinforcers, regardless of the presence or absence of the stimuli.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present experiment employed pigeons in an observing paradigm and sought to determine whether spatial information would be reinforcing if it indicated which of two keys must be pecked to produce food. Previous experiments employing pigeons have shown that the temporal information provided when the observing response produces an S+ is necessary to support the observing response, whereas production of an S-suppresses pigeons' observing responses (e_g., Dinsmoor, Browne, & Lawrence, 1972;Mulvaney, Dinsmoor, JWaideh, & Hughes, 1974;but see Lieberman, 1972, or Schrier, Thompson, & Spector, 1980, for their quite different conclusions when monkeys are used as the subjects). Both the "information hypothesis" and conditioned reinforcement hypotheses of observing predict that certain kinds of temporal information (Le_, when the S+ occurs) will support observing_ The "information hypothesis" of observing, however, seems to be based on the idea that observing responses may be acquired and maintained when they provide the organism with information of any sort about primary reinforcement.…”
mentioning
confidence: 99%